Identity Development: Narrative Identity and Intergenerational Narrative Identity - Naif Ergün (Psikiyatride Güncel Yaklaşımlar, 2020)
The aim of this study is to examine the development of identity and the role of identity theories on identity in the related literature. In Erikson's psychosocial identity theory, it is emphasized that the variables in the biological-individual-social aspects of the individuals are critical in ego identity formation. The theorists who came after Erikson and were influenced by his ideas were predominantly focused on one aspect of identity in their identity studies. In the developmental psychology literature, individual-internal factor centered theories have been put forward in the identity formation. In the last three decades, it is seen that narrative theorists have holistically studied Erikson's theory by examining identity formation and development. In the narrative identity form, individuals form a story based on their past experiences, and they live and form an identity according to the story they create. Individuals have the chance to express the relationship of all the variables in their identity formation because they narrate all the variables related to their identities through narratives. Narrative theorists have tried to clarify that self-stories, inter-generational stories, master narrative, historical and social events form an identity.